MAKNA RAGAM BAHASA JEPANG DANSEIGO DALAM KOMIK DORAEMON VOLUME 3 - Vamelia Aurina Pramandhani (Universitas Aki, 2021)
Japanese has a different form of conversational skills from other languages ​​in the world, namely the Danseigo language variety and the Joseigo language variety. Danseigo is a language variety that is often used by men in Japan when communicating. Danseigo is a male language that tends to be rude and informal. Danseigo is rarely found during formal events. Usually men use standard Japanese or use keigo if the other person is a respectable person. The formulation of the problem in this study is what is the meaning and function of shuujoshi in danseigo found in the Doraemon comic volume 3? The purpose of this research is to find out the meaning and function of shuujoshi in danseigo found in Doraemon comic volume 3. The research method used is descriptive qualitative. The source of data used in the analysis of this research is a written source, namely the comic